Transcriptomic analyses reveal the potential antibacterial mechanism of citral against Staphylococcus aureus - Liao, Zedong; Lin, Keshan; Liao, Weijiang; Xie, Ying; Yu, Guoqing; Shao, Yan; Dai, Min; Sun, Fenghui (Frontiers in Microbiology, 2023)
The emergence of multi-drug resistant Staphylococcus aureus (S. aureus) has posed a challenging clinical problem for treating its infection. Citral is reported to have antibacterial activity against S. aureus, but its mechanism is yet entirely clear. Herein, we conducted transcriptomic analysis and physiological trials to reveal its potential antibacterial mechanism. A total of 659 differentially expressed genes were identified, which included 287 up-regulated genes, enriching to oxidoreductase activity and fatty acid degradation pathway, and 372 down-regulated genes, enriching to ribosome and Staphylococcus aureus infection pathway. Physiological trials revealed a decline in ATP and protein levels within the citral-treated group. Meanwhile, the reactive oxygen species (ROS) content increased compared to the non-treated group. Our findings suggested that the antibacterial effects of citral against S. aureus were likely due to its ability to decrease ATP content by down-regulating ATP synthase genes (atpD and atpG), reduce protein content, induce cell membrane and cell wall damages, accumulate ROS, and down-regulate virulence factor genes to reduce pathogenicity. Therefore, the antibacterial mechanism of citral was likely a type of multi-target mode that affected multiple molecular processes in S. aureus.